Die Simfonie-orkes in die Psalmbundel. Psalm 150 as grand finalé in die Psalmbundel (Afrikaans) - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2013)
Dissertation (MA (Ancient Languages))--University of Pretoria, 2005.